A Supramolecular Radical Dimer: High‐Efficiency NIR‐II Photothermal Conversion and Therapy. Issue 43 (13th September 2019) - Tang, Bohan; Li, Wan‐Lu; Chang, Yincheng; Yuan, Bin; Wu, Yukun; Zhang, Ming‐Tian; Xu, Jiang‐Fei; Li, Jun; Zhang, Xi
Abstract: Photothermal therapy at the NIR‐II biowindow (1000–1350 nm) is drawing increasing interest because of its large penetration depth and maximum permissible exposure. Now, the supramolecular radical dimer, fabricated by N, N′‐dimethylated dipyridinium thiazolo[5, 4‐d]thiazole radical cation (MPT .+ ) and cucurbit[8]uril (CB[8]), achieves strong absorption at NIR‐II biowindow. The supramolecular radical dimer (2MPT .+ ‐CB[8]) showed highly efficient photothermal conversion and improved stability, thus contributing to the strong inhibition on HegG2 cancer cell under 1064 nm irradiation even penetrating through chicken breast tissue. This work provides a novel approach to construct NIR‐II chromophore by tailor‐made assembly of organic radicals. It is anticipated that this study provides a new strategy to achieve NIR‐II photothermal therapy and holds promises in luminescence materials, optoelectronic materials, and also biosensing. Abstract : Host‐enhanced intermolecular charge transfer enabled the fabrication of a supramolecular radical dimer with strong absorption in the NIR‐II biowindow and high stability. The dimer exhibited high‐efficiency photothermal conversion and strong inhibition on cancer cells through NIR‐II photothermal therapy.